Influence of art education on improving communication skills of multiple sclerosis (MS) patients - Baranauskienė, Ingrida; Kazlauskas, Andrius; Miliūnienė, Lina; Mockevičienė, Daiva; Radzevičienė, Liuda; Vaitkevičius, Jūra Vladas (Social Welfare: Interdisciplinary Approach, 2011)
The presented results reveal the dimensions of influence of art education on the improving of communication skills in patients with MS. Applied art education activities based on the pilot research data proved that personal motivation for an active participant in social life could be promoted by optimizing communication skills. All too often, problems of communications skills in MS first of all are linked to somatic and neurological problems, but from the point of view of social paradigm – person’s communication problems deal with effective social participation and social involvement into the society. The aim of the research is to prove and reveal changing characteristics of communication skills of MS persons under the influence of art education.
Keywords: Patients with MS; communication dimensions; art based education